Emotion regulation and sport performance - Wagstaff, C. R. D. (Journal of Sport & Exercise Psychology, 2014)
This study used a single-blind, within-participant, counterbalanced, repeated-measures design to examine the relationship between emotional self-regulation and sport performance. Twenty competitive athletes completed four laboratory-based conditions; familiarization, control, emotion suppression, and nonsuppression. In each condition participants completed a 10-km cycling time trial requiring self-regulation. In the experimental conditions participants watched an upsetting video before performing the cycle task. When participants suppressed their emotional reactions to the video (suppression condition) they completed the cycling task slower, generated lower mean power outputs, and reached a lower maximum heart rate and perceived greater physical exertion than when they were given no self-regulation instructions during the video (nonsuppression condition) and received no video treatment (control condition). The findings suggest that emotional self-regulation resource impairment affects perceived exertion, pacing and sport performance and extends previous research examining the regulation of persistence on physical tasks. The results are discussed in line with relevant psychophysiological theories of self-regulation and fatigue and pertinent potential implications for practice regarding performance and well-being are suggested.